COMPARATIVE STUDY ON FISCAL-ADMINISTRATIVE SOLICITOR'S OFFICE AND FISCAL SOLICITOR'S OFFICE - OCTAVIA MARIA CILIBIU (Challenges of the Knowledge Society)
The fiscal-administrative solicitor's office represents the activity of solving litigations between tax payers and the fiscal administration, litigations whose purpose is to cancel totally or partially a fiscal administrative document, document considered by the tax payer harmful for his legitimate right or interest recognized by law. The fiscal solicitor's office represents the activity of solving litigations whose purpose is to cancel or correction of acts of enforcement of tax claims. Research goal is to identify of the two institutions as many times between them is confusing. Study objectives: analysis the current stage of research in the field, definition of fiscal-administrative solicitor's office, definition of fiscal solicitor's office, the identification of elements similarity, the identification differences between the two institutions.